5D.04: NON PHARMACEUTICAL STRESS MANAGEMENT AND LIFESTYLE CHANGE PROGRAM MME (HEAL STRESS STUDY) FOR BLOOD PRESSURE CONTROL AND PSYCHOSOCIAL WELLBEING IN 553 PATIENTS IN ATTICA, GREECE. (June 2015) - Darviri, C.; Artemiadis, A.; Soldatos, P.; Protogerou, A.; Vasdekis, S.; Varvogli, L.; Michou, M.; Nasothymiou, E.; Kraniotou, C.; Karantzi, E.; Linardatou, A.; Vasilopoulou, E.; et al.
Abstract : Objective: Cardiovascular disease is the principal cause of death worldwide. Although the dose-response relationship between stress and hypertension is well established, there is a paucity of non-pharmaceutical intervention programs. The purpose of this study was to investigate the effectiveness of a stress management and lifestyle change program on blood pressure (BP) control and psychosocial wellbeing. Design and method: This was a quasi-experimental design with a waitlist control group in Attica, Greece, which was funded from EPANAD 2007–2013 (N = 553, 50% women and mean age 52.4 ± 8.46 years). The study comprised of an 8-week stress management and lifestyle change program including weekly sessions of stress management, dietary counseling, physical exercise and psychoeducation. Pre- and post- intervention BP measurements and psychosocial wellbeing factors were assessed. Results: Post-intervention there was a statistically significant reduction in systolic BP levels (mean: 126.05 vs 129.37, p < 0.001, intervention (IG) and control (CG) group, respectively). A 35.7% of the IG receded BP category vs. 17.5% of the CG (p < 0.001). After controlling for gender, age, educational level and BP cutoffs, we found significant improvements in stress, anxiety, self-esteem, spirituality, body weight, hours of sleep and in the subscales of the Healthy Lifestyle and Personal Control Questionnaire. Concerning the sub-categories of chance and powerful others in the health locus of control scale, improvements were recorded for the individuals of tertiary education. Conclusions: This non-pharmaceutical stress management and lifestyle change program resulted in significant benefits for regulation of BP, as well as for body weight, lifestyle and the psychosocial wellbeing of the participants. Future non-pharmaceutical programs are strongly encouraged both for the clinical and the community settings.